Experimental study on bond strength failure of GFRP lap joints. Issue 1 (1st February 2022) - Xiao, Xiao; Xiong, Gui; Dang, Hao
Abstract: Bonding has many advantages such as high adhesive strength, peel resistance, good toughness, shrinkage and corrosion-resistance, compared with bolting, welding and other connection patterns, which is the basic connection of the composite materials. The mechanical properties of the bond depend on the type and geometric parameters of the bond. In this paper, experiments were conducted to study the bond strength failure of GFRP single and double lap joints and explore related influencing factors. The variable factors of test specimens include bond type, length and thickness. The quasi-static tensile test was carried out at room temperature to analyze multiple influencing factors of lap joints and characteristic of GFRP bond failure strength. The results showed that the failure of the bond usually occurred at the interface of bond, and bond types, length and thickness have significant effects on the failure of bond. Failure strength increased firstly and then decreased with the increase of adhesive thickness. With the increase of bonding length, the failure mode of the double-lap joint become complex failure mode, which is accompanied by GFRP delamination near the surface of fiber of the bonding.